Schistosomiasis and the risk of bladder cancer in Alexandria, Egypt. - Bedwani, R. (Nature Publishing Group, 1998)
The relationship between history of schistosomiasis and bladder cancer risk was investigated using data from a case-control study conducted between January 1994 and July 1996 in Alexandria, Egypt. Cases were 190 subjects with incident, histologically confirmed invasive cancer of the bladder, and controls were 187 subjects admitted to hospital for acute, non-neoplastic, non-urinary tract conditions. Eighty-six cases (45%) vs 69 controls (37%) reported a history of urinary schistosomiasis. The corresponding multivariate odds ratio (OR) of bladder cancer -- after allowance for age, sex, education, smoking, other urinary infections and high-risk occupations -- was 1.72 (95% confidence interval (CI) 1.0-2.9). The ORs were 0.22 (95% CI 0.1-0.4) for intestinal schistosomiasis and 0.32 (95% CI 0.1-1.9) for schistosomiasis of other types. The OR for urinary schistosomiasis was higher in subjects who were younger at first diagnosis (OR of 3.3 for <15 years) and in those with a long time since first diagnosis (OR of 3.0 for > or = 35 years). The ORs were 15.8 for male ever-smokers with a history of urinary schistosomiasis, compared with never-smokers without such a history, and 3.2 for men ever-infected with urinary Schistosoma haematobium and ever-employed in high-risk occupations, compared with those never-infected and with no high-risk occupational history. This study confirms that clinical history of urinary schistosomiasis is significantly, but modestly, associated with increased bladder cancer risk, explaining some 16% of bladder cancer cases in this Egyptian population.